Determinasi Motivasi Dan Kinerja: Analisis Kompensasi, Kepemimpinan Dan Promosi Jabatan (Study Pada PT. Sari Dumai Sejati) - Teddy Chandra; Iqbal Miftakhul Mujtahid; Nico Gunawan (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
The purpose of this study was to determine the effect of compensation, leadership and promotion on employee motivation and performance at PT. SDS. The research population is employees who work at PT. SDS. The sampling technique used a proportional stratified random sampling technique with a total sample of 90 people calculated using the slovin method. The analysis technique used is structural equation modeling - partial least square (SEM-PLS) using the Warp-PLS program. The results of this study indicate that compensation, leadership and promotion have an effect on compensation and performance and show that compensation also affects performance, reinforced by the influence of compensation, leadership and promotion.